Protein synthesis elongation factor Tu present in spores of Streptomyces coelicolor can be phosphorylated in vitro by the spore protein kinase - Holub, M; Bezousková, S; Kalachová, L; Weiser, J (Folia microbiologica, 2007)
In vitro phosphorylation of EF-Tu was shown in cell-free extract from dormant spores of Streptomyces coelicolor by a protein kinase present in spores. EF-Tu phosphorylation was observed on both intrinsic S. coelicolor factor and externally added purified EF-Tu from S. aureofaciens, on two isoforms. Putative serine and threonine residues as potential phosphorylation targets were determined in primary sequence and demonstrated on 3D structure model of EF-Tu.
Keywords: 2D gelová elektroforéza; Protein Structure, Tertiary; zobrazování trojrozměrné; Imaging, Three-Dimensional; elongační faktor Tu; sekvence aminokyselin; terciární struktura proteinů; Molecular Sequence Data; Spores, Bacterial; proteinkinasy; Amino Acid Sequence; Streptomyces coelicolor; Models, Molecular; molekulární sekvence - údaje; molekulární modely; Peptide Elongation Factor Tu; fosforylace; Sequence Alignment; Electrophoresis, Gel, Two-Dimensional; Protein Kinases; Streptomyces aureofaciens; spory bakteriální; sekvenční seřazení; Phosphorylation